Silicene on substrates: A theoretical perspective*Project supported by the National Natural Science Foundation of China (Grant Nos. 11274016 and 11474012), the National Basic Research Program of China (Grant Nos. 2013CB932604 and 2012CB619304), and the National Natural Science Foundation of China (Grant No. 1207141). (August 2015) - Zhong, Hong-Xia; Quhe, Ru-Ge; Wang, Yang-Yang; Shi, Jun-Jie; Lü, Jing
Abstract Silicene, as the silicon analog of graphene, is successfully fabricated by epitaxially growing it on various substrates. Like free-standing graphene, free-standing silicene possesses a honeycomb structure and Dirac-cone-shaped energy band, resulting in many fascinating properties such as high carrier mobility, quantum spin Hall effect, quantum anomalous Hall effect, and quantum valley Hall effect. The existence of the honeycomb crystal structure and the Dirac cone of silicene is crucial for observation of its intrinsic properties. In this review, we systematically discuss the substrate effects on the atomic structure and electronic properties of silicene from a theoretical point of view, especially with emphasis on the changes of the Dirac cone.